The Effect of Entrepreneurial Knowledge and Environmental Support on Student Entrepreneurial Intention - Miswanto Miswanto; Shofia Suparti; Yanuar Rifqi Abdullah (Telaah Bisnis, 2020)
Abstract This study aims to examine the effect of entrepreneurial knowledge and environmental support on student entrepreneurship intentions. This study is a causal associative research with a quantitative approach. The variables of this study are entrepreneurial knowledge and environmental support as independent variables, entrepreneurship intentions as the dependent variable. This study is a research with 105 student respondents. Data collection techniques use questionnaire. Data analysis method used is regression. The results of this study indicate that (1) Entrepreneurial knowledge has a positive effect on entrepreneurial intentions and (2) Environmental support has a positive effect on entrepreneurial intentions. Therefore, the findings are that the knowledge and support of the environment has a positive effect on student entrepreneurship intentions.